Student assistance policies and school permanence in a Federal Institute (Research, Society and Development, 2022)
This article aims to investigate the importance of student assistance policies for the permanence of  students in the  first year  of Integrated High School (EMI)  at a Federal Institute. It is a qualitative and quantitative study, and the instrument used for data collection was a questionnaire designed to carry out this study. Data analysis was performed using descriptive statistics and content analysis. It was identified that there is a contradiction about the knowledge that students have about student assistance policies and those that are developed in the institution. In addition, for students, the resources available to access student assistance information are partially satisfactory. And yet, students consider student assistance policies to be relevant to stay at the institution. Based on the aspects studied, it is concluded that student assistance policies have a positive impact on the permanence of students, not only by making financial resources available, but also by offering actions that contemplate all dimensions of the subjects, allowing them to develop fully. These policies mainly in professional education are presented as instruments for overcoming dualistic education and for the democratization of education.